Heroes, gods & emperors from Roman mythology - Usher, Kerry; Sibbick, John (New York : Bedrick, 1992)
Retells 25 myths and legends of Rome and includes an index to the people and places in the stories and a guide to the symbols in the illustrations, plus map.
Horn Book.
School Library Journal.
Wilson's Junior High School.
7.5
5-8
7-9
Keywords: Mythology, Classical; Mythology, Roman; Classical mythology; Gods and goddesses; Heroes and heroines